If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -2x = 9(x + -1) Reorder the terms: 13 + -2x = 9(-1 + x) 13 + -2x = (-1 * 9 + x * 9) 13 + -2x = (-9 + 9x) Solving 13 + -2x = -9 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 13 + -2x + -9x = -9 + 9x + -9x Combine like terms: -2x + -9x = -11x 13 + -11x = -9 + 9x + -9x Combine like terms: 9x + -9x = 0 13 + -11x = -9 + 0 13 + -11x = -9 Add '-13' to each side of the equation. 13 + -13 + -11x = -9 + -13 Combine like terms: 13 + -13 = 0 0 + -11x = -9 + -13 -11x = -9 + -13 Combine like terms: -9 + -13 = -22 -11x = -22 Divide each side by '-11'. x = 2 Simplifying x = 2
| 3x+17y=51 | | 5x^2-18=0 | | -5x+6=5 | | x^3+9x^2+2x+18= | | -3x=2x-19 | | 4n^2-1=16 | | -.40p+2=.20p+11 | | -1x=19 | | 8x+4y-5x-7y= | | 3r(8r-3)=0 | | 5y=-2y-2 | | -9x^2+18x-16=0 | | -6x=0.5x^2-16 | | X+33=2(x)-12 | | f+3*3.14=12*3.14 | | 5x^4+3x^3+25x-15= | | 7(x-3)-3(x+2)=0 | | .5(7x+14)=1.8-(x+2) | | 32m^3n^4+20mn^2= | | 8-6m=3m-1 | | y^3z+y^2z^2-5y^2z-5yz^2= | | (4n+1)=12 | | (-a+3)=-2(2a+1)-7 | | -4(-7x+1)+5(8-4x)=-4 | | 3(y+1)=4 | | 7x^2+3x-54=0 | | 18x^2+2x-0.07=0 | | 3x^2-7x-1.25=0 | | 543x+22=346 | | 8x-3=6x-5 | | 6k-4k=4 | | 3x+30y=2 |